1999
DOI: 10.3354/dao037209
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with thiamine hydrochloride and astaxanthine for the prevention of yolk-sac mortality in Baltic salmon fry (M74 syndrome)

Abstract: Two practical methods are reported for treating feral Baltic salmon with thiamine hydrochloride against M74 syndrome (abnormally high yolk-sac fry mortality of the Baltic salmon). Both bathing of the yolk-sac fry in thiamine hydrochloride (1000 mg 1-l, 1 h) and a single intraperitoneal injection given to the female brood fish (100 mg kg-' fish) during the summer 3 mo before stripping were shown to elevate the whole body total thiamine concentration in the fry. Both treatments were also shown to be effective in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
26
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 12 publications
(16 reference statements)
1
26
0
Order By: Relevance
“…This is also typical for M74 (see e.g. [8]). The cumulative yolk-sac mortality of the offspring of the farmed females can be regarded as typical for farmed salmon at the Lautiosaari State Fish Hatchery (unpublished statistics of the farm).…”
supporting
confidence: 62%
See 4 more Smart Citations
“…This is also typical for M74 (see e.g. [8]). The cumulative yolk-sac mortality of the offspring of the farmed females can be regarded as typical for farmed salmon at the Lautiosaari State Fish Hatchery (unpublished statistics of the farm).…”
supporting
confidence: 62%
“…In this study the broodfish were all of the same strain, which makes a genetic aetiology even more unlikely than in the larger material of [12,8] found that injection of female broodfish with astaxanthine caused a proportionally greater decrease in thiamine concentration during the development of their offspring from newly fertilized eggs to yolk-sac fry. There might be also other effects of this kind on thiamine metabolism, some of which could be mediated by the male.…”
mentioning
confidence: 87%
See 3 more Smart Citations